A Strength-Based Intervention to Increase Participation in Leisure Activities in Children with Neuropsychiatric Disabilities: A Pilot Study - Anna Ullenhag; Mats Granlund; Lena Almqvist; Lena Krumlinde-Sundholm (Occupational Therapy International)
The aim is to evaluate the feasibility of an intervention model with a client-centered goal-directed approach with the aim to enhance the child’s participation in leisure activities, self-efficacy, and activity performance. A pilot intervention using a client-centered goal-directed approach and a single-subject design was performed. Two Swedish boys with neuropsychiatric diagnosis aged 12 and 14 years old were included, and 3 leisure activity goals were identified. The intervention was carried out over 8 weeks and took place in the adolescent’s everyday environment and at the pediatric rehabilitation center. The goal attainment of participation goals (GAS), the perceived performance ability according to the Canadian Occupational Performance Measure (COPM), the self-efficacy, and the participants’ satisfaction were used to study the effect. The participants succeeded in attaining their leisure goals as specified by the GAS by achieving +2 on one goal and +1 on the other two goals. They estimated higher performance ability and self-efficacy in their goal performance. Participants, parents, and therapists were overall satisfied and found the intervention to be applicable and helpful in optimizing leisure participation. The intervention model with a client-centered goal-directed approach in which participants define their own leisure activity goals appears to be effective in increasing participation in leisure activities.